2020
DOI: 10.3389/fpsyg.2020.01746
|View full text |Cite
|
Sign up to set email alerts
|

Findings From the International Lucid Dream Induction Study

Abstract: The International Lucid Dream Induction Study (ILDIS) investigated and compared the effectiveness of five different combinations of lucid dream induction techniques including reality testing (RT), Wake Back to Bed (WBTB), the Mnemonic Induction of Lucid Dreams (MILD) technique, the Senses Initiated Lucid Dream (SSILD) technique, and a hybrid technique combining elements of both MILD and SSILD. Participants with an interest in lucid dreaming (N = 355) completed a pre-test questionnaire and then a baseline sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Lucid dreaming is a specific phenomenon of dream consciousness that has been defined as the experience of knowing one is dreaming while one is dreaming ( LaBerge, 1985 , 2009 ). This has been described throughout human history and is a field of growing scientific interest ( Van Eeden, 1913 ; LaBerge, 1990 ; Harb et al, 2016 ; Saunders et al, 2016 ; Aspy, 2020 ; Yu and Shen, 2020 ; Ferreira et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lucid dreaming is a specific phenomenon of dream consciousness that has been defined as the experience of knowing one is dreaming while one is dreaming ( LaBerge, 1985 , 2009 ). This has been described throughout human history and is a field of growing scientific interest ( Van Eeden, 1913 ; LaBerge, 1990 ; Harb et al, 2016 ; Saunders et al, 2016 ; Aspy, 2020 ; Yu and Shen, 2020 ; Ferreira et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that deliberate control is possible in approximately one-third of LDs ( Soffer-Dudek, 2020 ; for example, changing location and deliberately waking up; Aspy, 2020 ), although it seems to be dependent on specific aspects of control (e.g., whether controlling the dream body or the environment) where higher rates were found ( Stumbrys and Erlacher, 2017 ). Stumbrys and Erlacher (2017) pointed out that full control over the dream plot is possible in about two-thirds of cases, while control of the dream environment and the ability to maintain dream awareness are possible in less than half of cases, where the main predictors of LD control were higher LD frequency and dispositional mindfulness in wakefulness, as well as younger age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, lucid dreaming therapy has recently been scrutinized for its potential negative impact due to occasional sleep interruptions and/or reality-fantasy questioning (Soffer-Dudek, 2020;Vallat & Ruby, 2019). Our data shows no relationship between lucidity and negative affect or subjective sleep quality (as in Aspy, 2020;Ribeiro et al, 2020;Schadow et al, 2018;Schredl et al, 2020;Stocks et al, 2020), however we did not implement measures of psychosis, which will be important for future lucid dream induction studies.…”
Section: Positive Impact Of Luciditymentioning
confidence: 55%
“…Moreover, conducting this sort of research in an experimental setting will help by shortening the temporal lag between experience and report (see De Vignemont, 2013) and thus, to meet with the gold standard of dream research of facilitating reports that are as close to the experience as possible. Although this might prove challenging, given the rarity and spontaneity of these sorts of experiences, future studies should investigate whether possible forms of objectless awareness like the one described here can be trained or be induced, like lucid dreaming (Voss et al, 2014;Sparrow et al, 2018;Aspy, 2020;Blanchette-Carrière et al, 2020).…”
Section: Strengths Shortcomings and Future Directionsmentioning
confidence: 99%